Some effects of tool geometric features on friction stir weld response parameters. (3rd October 2018) - Reza-E-Rabby, Md.; Reynolds, Anthony P.
ABSTRACT: Pin geometries (shape, dimensions, and surface features) have significant effects on friction stir welding, dictating, to some extent, the material flow which in turn affects process variables and joint quality. In this paper, volumetric defect content and process response variables (in-plane forces, torque, power, and temperature) as a function of pin thread forms and features (thread/flat/flute) on mildly tapered conical pins were examined in AA6061-T6 for a range of welding parameters. The coarser thread pitch with different pin features performed better for producing good quality welds compared to finer threaded pins. Forge force requirements can be minimised using counter-flow flutes in threaded pin. Variations of nugget geometry, torque, power, and temperature were reported to correlate their dependence on pin features.